Patterns of soil water repellency change with wetting and drying: the influence of cracks, roots and drainage conditions - Emilia Urbanek (Hydrological Processes, 2015)
The influence of simulated cracks and roots on soil water repellency (SWR) dynamics with and without basal drainage impedance in wetting–drying cycles was investigated in the laboratory experiments. Observations and measurements were taken following water application equivalent to 9.2-mm rainfall and then periodically during 80 h of drying. In total, 180 experiments were carried out using 60 samples of three homogeneous, reconstituted soils with different organic matter contents and textures, but of similar initial severity of SWR [18% molarity of an ethanol droplet (MED)]. Water flowing down the cracks and roots left the soil matrix largely dry and water repellent except for vertical zones adjacent to them and a shallow surface layer. A hydrophilic shallow basal layer was produced in experiments where basal drainage was impeded. During drying, changes in SWR were largely confined to the zones that had been wetted. Soil that had remained dry retained the initial severity of SWR, while wetted soil re-established either the same or slightly lower severity of SWR. In organic-rich soil, the scale of recovery to pre-wetting MED levels was much higher, perhaps associated with temporarily raised levels (up to 36% MED) of SWR recorded during drying of these soils. With all three soils, the re-establishment of the original SWR level was less widespread for surface than subsurface soil and with impeded than unimpeded basal drainage.Key findings are that as follows: (1) with unimpeded basal drainage, the soils remained at pre-wetting repellency levels except for a wettable thin surface layer and zones close to roots and cracks, (2) basal drainage impedance produced hydrophilic basal and surface layers, (3) thorough wetting delayed a return to water-repellent conditions on drying, and (4) temporarily enhanced SWR occurred in organic-rich soils at intermediate moisture levels during drying. Hydrological implications are discussed, and the roles of cracks and roots are placed into context with other influences on preferential flow and SWR under field conditions.